DEVELOPING AND IMPLEMENTING A MANDATORY ONLINE STUDENT ORIENTATION - Jones, Kona Renee (Online Learning, 2013)
A rural Community College evaluated their procedures for preparing students for online courses and determined they were not meeting the needs of the students. Through the use of the ADDIE Model of Instructional Design, a mandatory online orientation was developed and implemented. Results from the implementation indicate that after completing the orientation students feel they are better prepared for their online courses and this is further backed up by an increase in online retention.